The duffy antigen/receptor for chemokines exists in an oligomeric form in living cells and functionally antagonizes CCR5 signaling through hetero-oligomerization - Chakera, Aron; Seeber, R.; John, A.; Eidne, K.; Greaves, D. (2008)
The Duffy antigen/receptor for chemokines (DARC) is an unusual chemokine receptor that binds a large number of inflammatory chemokines of both the CC and CXC families with nanomolar affinity, yet it lacks the ability to signal upon ligand binding. Using bioluminescent resonant energy transfer, we have demonstrated for the first time that DARC exists as a constitutive homo-oligomer in living cells and furthermore that DARC hetero-oligomerizes with the CC chemokine receptor CCR5. DARC-CCR5 interaction impairs chemotaxis and calcium flux through CCR5, whereas internalization of CCR5 in response to ligand binding remains unchanged. These results suggest a novel mechanism by which DARC could modulate inflammatory responses to chemokines in vivo. Copyright © 2008 The American Society for Pharmacology and Experimental Therapeutics.